2016
DOI: 10.1051/matecconf/20164705025
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Organic Waste in Composting

Abstract: Abstract. This paper reviewed studies on the composting process of organic waste. Organic wastes are wastes that easily biodegradable. These wastes are produced from many sources such as agricultural waste, market waste, kitchen waste, urban solid food wastes and municipal solid waste. Without proper management, these waste could create several environment problem. Therefore, composting is the best low cost alternative solution to overcome this problem. Composting method can degrade all types of organic wastes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 10 publications
(14 reference statements)
1
29
0
5
Order By: Relevance
“…In terms of nutrient contents, phosphorous, potassium, calcium, sulfur, sodium, and magnesium are required for agriculture (Khan & Ishaq, 2011;Rama & Vasanthy, 2014). Different composting methods affect the nutrient status of the compost and its effects on soil content (Kadir et al, 2016).…”
Section: Compost Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of nutrient contents, phosphorous, potassium, calcium, sulfur, sodium, and magnesium are required for agriculture (Khan & Ishaq, 2011;Rama & Vasanthy, 2014). Different composting methods affect the nutrient status of the compost and its effects on soil content (Kadir et al, 2016).…”
Section: Compost Qualitymentioning
confidence: 99%
“…Organic waste or green waste can be defined as organic material that is easily biodegradable (Kadir et al, 2016). Organic material is derived from natural sources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported that it is essential to reduce food loss and food waste for the question of food security [75]. This can be done by using the fruit and vegetable waste at a retail and consumer level (supermarkets and food markets) as substrates in bioprocesses [88] to produce organic fertilizers [89,90], as long as this waste is treated correctly to reduce the environmental impact [91]. Compulsory regulation can set some quality standards to reduce waste [92].…”
Section: Conceptual Frameworkmentioning
confidence: 99%